1999
DOI: 10.1007/bf03161784
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative effects on wetland landscapes: Links to wetland restoration in the United States and southern Canada

Abstract: The cumulative effects of human actions on wetland ecosystems motivate current efforts at wetland restoration. They also have created in part the context within which restorations are undertaken. Using modern hydrogeological understanding of wetland-landscape linkages, I argue that restorations should begin with a cumulative impact analysis for the entire region in which the restoration is proposed. The analysis, however, should not focus merely on number of hectares of wetlands lost or degraded. It should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 74 publications
0
69
0
Order By: Relevance
“…Fens that have not been impacted by humans often host a diversity of plant species, many of which are locally or globally rare (Amon et al 2002;Johnson and Leopold 1994). Our previous work relating nutrient limitation to wetland plant diversity (Bedford 1999;Drexler and Bedford 2002;Drexler et al 1999) suggested that groundwater might influence plant diversity, in particular, through effects on soil phosphorus (P) availability.…”
mentioning
confidence: 99%
“…Fens that have not been impacted by humans often host a diversity of plant species, many of which are locally or globally rare (Amon et al 2002;Johnson and Leopold 1994). Our previous work relating nutrient limitation to wetland plant diversity (Bedford 1999;Drexler and Bedford 2002;Drexler et al 1999) suggested that groundwater might influence plant diversity, in particular, through effects on soil phosphorus (P) availability.…”
mentioning
confidence: 99%
“…Matthews and Endress (2008) suggested that the use of benchmarks could help agencies with permit approvals, selection of mitigation site locations, calculation of compensation ratios, development of performance criteria, and implementation of postconstruction monitoring protocols. Bedford (1999) argued that wetland restoration will be more successful if individual wetland restoration decisions are made in light of past and present regional profiles, and Olsen and Christie (2000) highlighted the importance of locally and socially relevant indicators to build local ownership of coastal (wetland) management, especially for direct users/abutters of wetlands. Watershed planning can also provide rich opportunities for more place-based and prescriptive restoration goals (Stanturf et al 2001;Olsen and Christie 2000), thereby addressing some of the competing goals (individual to structural) that limit overall restoration effectiveness.…”
Section: Watershed-based Planningmentioning
confidence: 99%
“…Thus, as a wetland landscape varies in scale, due perhaps to conversion, draining or other human-induced disturbances, the impact on the provision of and synergies between wetland services can be substantial. Such a landscape approach is being used increasingly for assessing the cumulative effects of wetland loss and degradation, characterizing wetland boundaries and identifying restoration or mitigation opportunities (NRC 1995, Bedford 1996, 1999, Gwin et al 1999, Mitsch and Gosselink 2000, Simenstad et al 2006. It follows that the various goods and services provided by a wetland will also be tied to, and thus defined by, its landscape extent; i.e.…”
Section: Maintenance Of Temperature Precipitationmentioning
confidence: 99%
“…Increasingly, a hydrologybased landscape approach is being used to assess the cumulative effects of wetland loss and degradation, characterizing wetland boundaries and identifying restoration or mitigation opportunities (Bedford 1996, 1999, Gwin et al 1999, Mitsch and Gosselink 2000, NRC 1995, Simenstad et al 2006. As emphasized in this paper, such an approach is consistent with the view of wetlands as natural assets that generate multiple ecosystem services.…”
Section: Final Remarksmentioning
confidence: 99%